Treatment of paroxysmal nocturnal hemoglobinuria - I. A. Lisukov; A. D. Kulagin; B. V. Afanasyev (Онкогематология, 2014)
Paroxysmal nocturnal hemoglobinuria (PNH) is a rare, life‑threatening clonal hematological disorder caused by an acquired mutation in the phosphatidylinositol glucan (PIG)-A gene. PNH is characterized by chronic intravascular hemolysis, marrow failure, thrombophilia and other severe clinical syndromes. Until recently, the treatment of PNH has been symptomatic with blood transfusions, anticoagulation and supplementation with folic acid or iron. The only potentially curative treatment is allogeneic stem cell transplantation, but this has severe complications with high mortality rates. A new targeted treatment strategy is the inhibition of the terminal complement cascade with anti‑C5 monoclonal antibody (eculizumab). Eculizumab has shown significant efficacy in controlling of intravascular hemolysis resulting in improving quality of life and survival.